Administrative data and scientific evidence: a lesson from France – the safety of systemic treatment for psoriasis during the COVID‐19 pandemic. (1st January 2022) - Cazzaniga, S.; Naldi, L.
Abstract: Linked Article: Penso et al . Br J Dermatol 2022; 186 :59–68 .